Information Technology Based Governance Model for Islamic Education Management in Realizing Contemporary Public Accountability - Cecep Hilman; Muh. Rizal Samad (Khazanah: Journal of Islamic Education and Science, 2025)
Digital transformation in the education sector has reshaped the governance paradigm of Islamic educational institutions, particularly in responding to contemporary demands for public accountability. This study aimed to develop an integrated information technology based governance model for Islamic education management that is responsive to principles of transparency, participation, and data-driven decision-making. The research employed a descriptive qualitative approach using a systematic literature review design of reputable scholarly articles published between 2016 and 2025, selected through a structured screening protocol. Data were analyzed using content analysis and thematic analysis to synthesize findings across studies. The results indicated that digital transparency, integrated information systems, digital leadership, stakeholder engagement, and data-driven accountability constituted the core components of accountable governance in Islamic education. The proposed model integrated input, process, and output dimensions into a coherent conceptual framework. This study contributed theoretically by advancing a technology-based governance model and contributed practically by providing strategic guidance for strengthening adaptive and accountable management in Islamic educational institutions within the digital era.